An annotated checklist of chewing lice (Phthiraptera: Amblycera, Ischnocera) from Slovakia - Ošlejšková, Lucie; Krištofík, Ján; Trnka, Alfréd; Sychra, Oldřich (Zootaxa, 2021)
This checklist includes taxa of chewing lice from published records, old collections, and recently collected material from birds and mammals in Slovakia. Data from established collections correspond to five different periods: (1) 1925–1939, collection of Karel Pfleger; (2) 1946–1978, collection of František Balát; (3) 1974–1985, collection of Vladimír Straka; (4) 1997–2012, collection of Ján Krištofík; and (5) 2008–2019, a collection made by the authors of this paper. A total of 255 species of feather lice—67 amblyceran species in 22 genera of families Laemobothriidae, Menoponidae and Ricinidae, and 188 ischnoceran species in 54 genera of the family Philopteridae—and 366 host-louse associations are listed from 171 bird species in 21 orders. In addition, eight species of chewing lice in five genera of the family Trichodectidae are listed from eight species of mammals. Species of chewing lice are reported from about 240 different locations throughout the territory of Slovakia. Also, 43 species of lice and 20 host-louse associations for Slovakia, as well as four host-louse associations for the world, are included as new records. A host-louse list of recorded species is also given.